Inflation dynamics: An econometric analysis of the Mexican heterodox adjustment - Arellano Cadena, Rogelio; González Castañón, Eduardo (Estudios Económicos de El Colegio de México, 1993)
This paper examines the recent inflationary process in the Mexican economy using two complementary approaches that avoid (somewhat) the restrictions imposed by structural models. The first approach applies a vector autoregressive process, while the second applies multivariate cointegration.